KARAKTERISTIK USAHATANI PETANI LOKAL DAN PETANI TRANSMIGRAN (STUDI KASUS: KAMPUNG SIDEY BARU DAN SIDEY PANTAI) - Deasi Mayawati; Sa'diyah, Siti Halimatus; Rifa Gabriella Makalew (Sosio Agri Papua, 2025)
This study aims to compare farming systems by identifying the characteristics of farming management applied by two groups of farmers, namely local farmers and transmigrant farmers in Sidey District, Manokwari Regency, West Papua Province based on patterns, forms, types and characteristics. The data analysis used is comparative and descriptive qualitative presented in simple tabulations. Data collection techniques through literature studies of farming data in two different villages. The results of the analysis show: based on age, it was found that local farmers with more productive ages than transmigrant farmers. The level of education possessed by local farmers is higher than that of transmigrant farmers, the number of dependents of family members owned by transmigrant farmers is greater than that of local farmers. The farming experience of transmigrant farmers is longer than that of local farmers. The form of farming of these two groups is individual (individual farm). The pattern of farming of both is commercial with local farmers' income lower than that of transmigrant farmers. According to the farming pattern, local farmers have a mixed farming pattern and transmigrant farmers have a special farming pattern. According to type, transmigration farmers operate their farming businesses on both wet and dry land, while local farmers predominantly operate their farming businesses on dry land.